Effect of Hevin Deletion in Mice and Characterization in Trabecular Meshwork - Kang, Min Hyung (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. Hevin is a matricellular protein and the result of a gene duplication of SPARC. SPARC-null mice have lower intraocular pressure (IOP). The function of hevin in trabecular meshwork (TM) is unknown. The authors hypothesized that hevin is expressed in TM and has a functional consequence on IOP. METHODS. Reverse transcriptase-polymerase chain reaction (RT-PCR) and immunoblotting were performed to identify transcription and protein expression in TM and cultured TM cells. Toluidine blue stain was performed to compare anterior segments in wild-type (WT) and hevin-null mice. Confocal microscopy localized the structural distribution of hevin in human TM and hevin/SPARC in mouse anterior segments. IOP was measured in WT (C57BL6 × 129SvJ) and hevin-null mice using both rebound tonometry and cannulation tonometry. Central corneal thickness (CCT) was measured by ocular coherence tomography. Cultured TM cells were treated with TGF-β2 because TGF-β2 is associated with primary open-angle glaucoma. RESULTS. Hevin mRNA and protein were expressed in TM tissues but not in cultured TM cells. No structural differences were observed in anterior segments of WT and hevin-null mice. IOP between hevin-null (n = 46) and WT (n = 44) mice was equivalent (15.3 ± 1.92 mm Hg and 15.9 ± 2.01 mm Hg, respectively; P = 0.15). CCT was similar between hevin-null and WT mice (107.95 ± 5.06 μm and 106.76 ± 3.46 μm, respectively; P = 0.11). TGF-β2 did not induce hevin, whereas SPARC expression was induced in a dose-dependent manner in human TM cell cultures. CONCLUSIONS. Hevin does not appear to be critical to regulating IOP. Hevin is expressed in TM but, in contrast to SPARC, does not appear to be regulated by TGF-β2.